A critical review of food-associated factors proposed in the etiology of feline hyperthyroidism. Issue 10 (October 2015) - van Hoek, Ingrid; Hesta, Myriam; Biourge, Vincent
Since the first description of feline hyperthyroidism (HT) in 1979, several studies have been undertaken to define the etiology of the disease. Epidemiologic studies, after investigating non-food- and food-associated factors, suggest a multifactorial etiology. However, in the absence of prospective cohort studies that can confirm a cause-and-effect relationship between HT and associated risk factors, no causative factor for HT has been identified to date. Feline HT resembles toxic nodular goiter in humans, with autonomously functioning upregulated iodide uptake systems. Contribution of the diet to HT development remains controversial. The purpose of this paper is to review critically the reported food-associated risk factors for HT.